Schelling's naturalism : space, motion and the volition of thought - Woodard, Ben (New prespectives in ontology., 2019)
Using Schelling's philosophy, Ben Woodard examines how an expanded form of naturalism changes how we conceive of the division between thought and world, mathematics and motion, sense and dynamics, experiment and materiality, as well as speculation and pragmatism.